Closing the Gap in Education and Technology - De Ferranti, David; Perry, Guillermo E.; Gill, Indermit; Guasch, J. Luis; Maloney, William F.; Sanchez-Paramo, Carolina; Schady, Norbert (Washington, DC: World Bank, 2013)
This report focuses not only on the gaps facing Latin America in both education and technology, but especially on the interactions between the two. The central premise of the report is that skills and technology interact in important ways, and this relationship is a fundamental reason for the large observed differences in productivity and incomes across countries. This report argues that skills upgrading technological change, and their interaction are major factors behind total factor productivity growth. Skill-biased technological change is indeed being transferred today at faster speeds to LAC countries, as elsewhere. Technological change has been complementary with skill levels in Latin America in the last two decades. It is further estimated that firms have substantially increased the demand for educated workers in the region, particularly workers with tertiary education. This technological transformation appears to be intimately related to patterns of integration in the world economy. Firms in sectors with higher exposure to trade are subject to more competitive pressures. Adopting and adapting more advanced technologies and hiring and training more educated workers is one way to respond to this pressure to become more productive. The increased potential demand for education offers the possibility to accelerate productivity growth in the economy by closing the educational and technological gaps that Latin American countries exhibit with respect to their peers.